Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
This will need become a point slope form.
First we need to find slope
(Y2-Y1/X2-X1)
(8-5/4-0) = (3/4)
Slope = (3/4)
Now for the point slope equation
y - y1 = m(x-x1)
Plug in one of the points and the slope
y - (5) = 3/4(x - (0))
Let’s convert to y = mx + b formatting
y - (5) = 3/4(x - (0))
y - 5 = 3/4x - (3/4)(0)
y - 5 = 3/4x
y = 3/4x + 5
This will be your equation.
First we need to find slope
(Y2-Y1/X2-X1)
(8-5/4-0) = (3/4)
Slope = (3/4)
Now for the point slope equation
y - y1 = m(x-x1)
Plug in one of the points and the slope
y - (5) = 3/4(x - (0))
Let’s convert to y = mx + b formatting
y - (5) = 3/4(x - (0))
y - 5 = 3/4x - (3/4)(0)
y - 5 = 3/4x
y = 3/4x + 5
This will be your equation.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.